Pengaruh Literasi Keuangan, Gaya Hidup Hedonisme, dan Pendapatan Terhadap Perilaku Keuangan Pribadi Pada Mahasiswa di Kota Bandung - Suryani, Tiwi; Damayanti, Santi (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the effect of financial literacy, hedonistic lifestyle, and income on students' personal financial behavior in Bandung City. The research applies a quantitative approach using a survey method with questionnaires distributed to 96 student respondents. Data analysis techniques include descriptive statistics, Pearson correlation, and multiple linear regression. The results reveal that all three independent variables simultaneously have a significant effect on students' financial behavior. Partially, financial literacy, hedonistic lifestyle, and income each have a significant positive influence. These findings emphasize the importance of improving financial understanding, controlling consumerist lifestyles, and managing income to build healthy personal financial behavior.